A Mathematical Model for Waste Management in Reverse Supply Chain - Zahra , Hosseini; Hamed , Fazlollahtabar; Iraj , Mahdavi; Minhat, Mohamad (2013)
Reverse supply chain problem is one of the issues in supply chain which as well explore wastes management in relation to customer. In reverse supply chains, wastes can be recycled and reproduced and benefiting from profitability of new products which is produced from it. In this study, residuals, after transferring by customer, send to production station, sorting station and different manufacturing processes (melting, forging, clamping, painting …) for reproduction. After completion of all different manufacturing processes, several diverse products resend to customers. Here, with respect to different cost factors and also pricing concept and reproduced parts, we evaluate the mathematical model of optimizing manufacturing cost. The solution will be useful for strategic decision making in municipalities